ANALISIS PERUBAHAN KONSENTRASI NITROGEN DIOKSIDA (NO2) PADA AREA BERVEGETASI DAN TIDAK BERVEGETASI DI JALAN SIMPANG SUSUN - Farida Dwirahmawati; Nizar Nasrullah; Bambang Sulistyantara (http://arl.faperta.ipb.ac.id/, 2018)
The Interchange of highway is the intersection of several roads that consists of numerous road levels. It causes great number of traffic volume and releases vast pollutant quantities. This research objective were to analyze the influence of wind speed and traffic volume with NO2 concentrations at the surrounding of the interchange road. Researches were conducted at Cikunir interchange, between JORR E1 (Taman Mini-Cikunir segment), JORR E2 (Cikunir-Cakung), and Jakarta-Cikampek toll road. Concentration of NO2 gas was measured at the point of 0 m, 10 m, and 75 m from the shoulder in the green belt plot and in the plot having no green belt. The results showed that there is a significant correlation between traffic volume with ambient NO2 concentration. The correlation level between the volume of vehicle with NO2 concentration is 0.925 (very strong). Wind speed did not have a significant correlation with NO2 concentrations. Volume of vehicles and wind speed simultaneously (together) have a significant correlation on the NO2 concentration.